Prevention of gravidic endothelial hypertension by aspirin treatment administered from the 8th week of gestation - Bakhti, Abdelouahab; Vaiman, Daniel (Hypertension research, 2011)
The aim of this study was to evaluate whether low doses of aspirin (100 mg per day) administered to a homogeneous population of women early (8-10 weeks) during their first pregnancy improved the outcome of gestation hypertensive disorders. This study was performed at the Blida Hospital, where many early deliveries and pregnancy complications are observed. A total of 164 women were either treated (82) or used as controls (82). Treatment increased the gestation length by 12 days on average, thus triggering an approximate 150-g increase in newborn weight. This consistently improved the outcome for all patients with respect to all parameters investigated. Overall, the relative risk of developing hypertensive disorders of gestation was reduced to 0.07 (confidence interval=0.01-0.51). In our series, we did not observe deleterious consequences for the fetus (teratogenicity and fetotoxicity) or adverse outcomes for the mothers. Despite the limited number of patients analyzed, the present study is one of the largest investigating early aspirin treatment of gestational hypertensive diseases. In addition, the time of aspirin administration is among the earliest yet examined. The data tend to confirm the results obtained from other cohorts on the overall benefit of aspirin treatment for gestational disorders. In the future, molecular or ultrasonographic markers of these diseases could help to screen patients before applying the treatment.